2007
DOI: 10.1177/0095327x07312090
|View full text |Cite
|
Sign up to set email alerts
|

Reserve Soldiers as Transmigrants

Abstract: This article suggests a new perspective for examining the particular social and organizational characteristics of military reserves forces and the special experiences of serving in the reserves. To illustrate the unique social position of reservists, the authors develop a theoretical model that likens them to transmigrants. Accordingly, the authors suggest that society may benefit from looking at reserves both as sorts of social and organizational hybrids or amalgams-they are soldiers and civilians, they are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 21 publications
(9 reference statements)
0
26
0
4
Order By: Relevance
“…Taken together, the findings in the current study provide further evidence in support of the work by Lomsky-Feder et al, suggesting that research on regular force personnel may not be applicable to reservists. 2 These differences could be due to the way in which individuals in the current study identified with being a reservist or a member of the CAF. In particular, 64% of reservists studied stated they had not deployed.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Taken together, the findings in the current study provide further evidence in support of the work by Lomsky-Feder et al, suggesting that research on regular force personnel may not be applicable to reservists. 2 These differences could be due to the way in which individuals in the current study identified with being a reservist or a member of the CAF. In particular, 64% of reservists studied stated they had not deployed.…”
Section: Discussionmentioning
confidence: 91%
“…Th ey are likened to transmigrants -that is, individuals who leave their homeland to live in another country -because reservists are constantly moving from one sphere to another, similar to transmigrants who have a sense of belonging to both their homeland and new place of residence. 2 Connection to homeland, for a reservist, can be equated to affection and nostalgia for a regiment (history and traditions), and the significance of regimental ties. However, reservists also have ties to the civilian community via jobs, education, family, friends, and local networks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations